Particle swarm optimization based high performance four switch BLDC motor drive - Yaser Anagreh; Moath Bani Fayyad; Aysha Anagreh (Institute of Advanced Engineering and Science, 2022)
The present publication is directed to utilize particle swarm optimization (PSO) algorithm based PI controller for adjusting the speed of brushless DC motor fed via four switch three phase inverter. The inverter topology reduces the cost and complexity of the drive system. High performance response during transient and steady state conditions is achieved by optimizing the controller gains using POS algorithm. The obtained results confirm the validity of the proposed drive configuration in providing the features of fast dynamic response (the settling time is about 0.025 s), with minimized percentage overshot, and approximately zero steady state error. Moreover, the drive system shows robustness feature when subjected to external load torque disturbances.